2005
DOI: 10.1007/s10658-004-8232-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of specific PCR primers for identification and detection of Phytophthora capsici Leon

Abstract: A PCR-based method was developed for the identification and detection of Phytophthora capsici in pepper plants. Three PCR primers (CAPFW, CAPRV1 and CAPRV2) specific for P. capsici were designed based on the sequence of its internal transcribed spacer regions. CAPFW/CAPRV1 amplify a 452 bp product from P. capsici DNA whereas CAPFW/CAPRV2 a 595 bp fragment; neither set amplifies DNA from pepper or several fungi pathogenic to pepper. In conventional (single-round) PCR, the limit of detection was 5 pg DNA for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…These samples were all positive for the detection of P. capsici. The symptoms presented by the plants affected by this pathogen are -similar to the symptoms of Verticillium wilt which can lead to confusion (Silvar et al 2005b). We were unable to detect Verticillium dahliae in plots B2 and B3, where disease symptoms were slight, or in B5, where disease symptoms were not observed.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These samples were all positive for the detection of P. capsici. The symptoms presented by the plants affected by this pathogen are -similar to the symptoms of Verticillium wilt which can lead to confusion (Silvar et al 2005b). We were unable to detect Verticillium dahliae in plots B2 and B3, where disease symptoms were slight, or in B5, where disease symptoms were not observed.…”
Section: Discussionmentioning
confidence: 71%
“…We were unable to detect Verticillium dahliae in plots B2 and B3, where disease symptoms were slight, or in B5, where disease symptoms were not observed. Interestingly, P. capsici was detected in the two plants collected from greenhouse B2 (corresponding to Farm 4 in Silvar et al 2005b). Practical application of the described method seems clear, since it was possible to detect the pathogen in plants, soil and water before visible symptoms of the disease appeared.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, Silvar et al (2005) showed that sensitivity of detection of Phytophthora capsici could be significantly increased using nested-PCR compared to a conventional PCR assay. While in conventional PCR, the lowest amount of amplified DNA was 5 pg for the primers used, in the nested-PCR, the detection limit was 0.5 fg of template DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The biomass of P. capsici in the inoculated Arabidopsis leaf tissues was determined by qPCR during a time course (24, 36, 60, and 72 hpi) using Phytophthora-specific primers amplifying the ITS region (Silvar et al 2005). The primer pair AtRub-F4 and AtRub-R4 amplifying the gene encoding the large subunit of RuBisCo was used as the internal standard.…”
Section: P Capsici Infection Assay Of Arabidopsis Leavesmentioning
confidence: 99%